C# Quick Syntax Reference - Olsson, Mikael. (Apress : Imprint: Apress, 2013)
The C# Quick Syntax Reference is a condensed code and syntax reference to the C# programming language. It presents the essential C# syntax in a well-organized format that can be used as a handy reference. You won<U+0019>t find any technical jargon, bloated samples, drawn out history lessons or witty stories in this book. What you will find is a language reference that is concise, to the point and highly accessible. The book is packed with useful information and is a must-have for any C# programmer. In the C# Quick Syntax Reference, you will find: ʺ A concise reference to the C# language syntax. ʺ Short, simple and focused code examples. ʺ A well laid out table of contents and a comprehensive index allowing easy review.